DAMPAK BULLYING TERHADAP KESEHATAN MENTAL SISWA DAN IMPLIKASINYA DALAM BIMBINGAN KONSELING - Haniati Gowasa (Universitas Nias Raya, 2026)
This study was conducted to analyze the influence of bullying behavior on students’ mental health conditions and to understand its implications for the implementation of guidance and counseling services within the school environment. The research employed a qualitative approach with a descriptive analytical method. This study involved students who experienced bullying, counseling teachers, homeroom teachers, and parents selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The research findings indicate that the most common forms of bullying experienced by students include verbal, social, physical, and cyberbullying. The impacts experienced by students included anxiety, fear, low self-esteem, social withdrawal, and psychosomatic disorders such as sleep difficulties and loss of learning motivation. Bullying also affected students’ academic motivation and achievement. Guidance and counseling services help students recover mentally through counseling and emotional support.